2019
DOI: 10.3390/v12010022
|View full text |Cite
|
Sign up to set email alerts
|

Enterovirus 71 Represses Interleukin Enhancer-Binding Factor 2 Production and Nucleus Translocation to Antagonize ILF2 Antiviral Effects

Abstract: Enterovirus 71 (EV71) infection causes hand-foot-mouth disease (HFMD), meningoencephalitis, neonatal sepsis, and even fatal encephalitis in children, thereby presenting a serious risk to public health. It is important to determine the mechanisms underlying the regulation of EV71 infection. In this study, we initially show that the interleukin enhancer-binding factor 2 (ILF2) reduces EV71 50% tissue culture infective dose (TCID50) and attenuates EV71 plaque-formation unit (PFU), thereby repressing EV71 infectio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…However, the pandemic caused by SARS‐CoV‐2 is unprecedented. The mortality rates of SARS and MERS were > 10% and 35%, respectively 1 , 2 , while it is only 3.12–5.43% among the hospitalized COVID-19 patients according to the data from National Health Commission of the People's Republic of China and World Health Organization.…”
Section: Introductionmentioning
confidence: 99%
“…However, the pandemic caused by SARS‐CoV‐2 is unprecedented. The mortality rates of SARS and MERS were > 10% and 35%, respectively 1 , 2 , while it is only 3.12–5.43% among the hospitalized COVID-19 patients according to the data from National Health Commission of the People's Republic of China and World Health Organization.…”
Section: Introductionmentioning
confidence: 99%
“…2B could act directly to impact on the replication of enteroviruses. A recent report showed that EV-A71 2B interacted with transcription factor ILF2 in the cytoplasm to inhibit its negative regulation on virus RNA replication, suggesting that viral 2B could modulate EV-A71 replication in a direct manner (Jin et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The mature virion enters the endosome and interacts with toll-like receptors (TLR) from the immune cells to stimulate downstream inflammatory and clot pathways. Despite sharing almost 70% of the amino acid sequences of SARS-CoV-1, and having the same functional receptor (ACE2), SARS-CoV-2 is more contagious than SARS-CoV-1 and MERS-CoV [ 5 , 15 ]. It has two main genomic polymorphisms; the newest and the most predominant one, L type (∼ 70%) is meant to be more aggressive, and spreads quicker than others [ 14 , 16 , 17 ].…”
Section: Covid-19: An Immunological Disorder Underlying a Clinical Diseasementioning
confidence: 99%
“…SARS-CoV-2 is the seventh and the larger type of enveloped simple strained RNA coronavirus species that has been demonstrated to be able to infect humans [ 4 ]. The Severe Acute Respiratory Syndrome coronavirus 1 (SARS-CoV-1) and the Middle East respiratory syndrome coronavirus (MERS-CoV) are two zoonotic coronaviruses that were responsible for epidemic outbreaks with a great local impact in 2002 in China, and in 2012 in Saudi Arabia, respectively [ 5 ]. Their global impact, however, was relatively low.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation